Reaffirming Javanese Patriarchy: Gender Roles and Cultural Identity in K.H. Bisri Musthafa’s Tafsīr al-Ibrīz - Arinda Rosalina; Anwar Mujahidin (Dialogia, 2025)
This research examines the intersection between Qur'anic interpretation and Javanese culture, focusing on K.H. Bisri Musthafa’s Tafsīr al-Ibrīz, a commentary written in Javanese using pegon script. The study employs an in-depth analytical approach, addressing two key aspects: the representation of verses concerning gender relations (men and women), and the dynamic interplay between the interpreter’s perspective and the Javanese cultural framework. As a library-based study, this research adopts a descriptive-analytical method, utilizing hermeneutic theory to analyze the triad of text, interpreter, and socio-cultural context. The findings reveal that al-Ibrīz positions men as the leaders of the household, asserting their authority over women, who are expected to submit to male guardianship. The commentary emphasizes biological determinism: men are portrayed as physically strong and resilient, thus assigned the role of providers and protectors, while women are associated with gentleness and confined to domestic spheres—summarized in the Javanese culture as macak (grooming), masak (cooking), and manak (childbearing). Additionally, the interpretation highlights women’s reproductive functions, including menstruation, menopause, and breastfeeding obligations. The analysis confirms a cultural-textual synergy: the interpreter’s model aligns with traditional Javanese patriarchy, where men dominate household governance, and women occupy a subordinate position. REFERENCES Abu Syuqqah, Abdul Halim. Women's Freedom. Cet. 1. Jakarta: Echoes of Human Press, 1997. Amrullah et al., Najib. "Men are Leaders for Women (Study of Thematic Interpretation from the perspective of Mutawalli Al-Sya'rawi in Tafsir Al-Sya'rawi)." Al-Tadabbur: Journal of Al-Qur'an Science and Interpretation, tt https://doi.org/10.30868/at.v6i01.1336. Andika, Mayola. "Reinterpretation of Gender Verses in Understanding Male and Female Relations (Contextual Study of Q.S an-Nisā` Verse 34)." Journal of Dignity: Gender Communication Media 14, no. 1 (January 22, 2019): 12–20. Aunillah, Reza Pratama. "Women's Rights in Tafsir al-Ibrīz and Tafsir Tāj al-Muslimīn." Shuff Journal, December 2018, 31. https://doi.org/10.22548/shf.v11i2.359. Dahri, Nurdeni. "Women's Reproduction in an Islamic Perspective (Review of Menstruation, Nifas, and Istihadhah)." Marwah: Journal of Women, Religion, and Gender 11, no. 2 (November 2, 2012): 1–15. https://doi.org/10.24014/marwah.v11i2.504. Goddess, Ratna. "The Concept of Women's Reproductive Health in the Qur'an." Mawa'izh: Journal of Da'wah and Human Social Development, December 2019, 26. https://doi.org/10.32923/maw.v10i2.920. Djamaluddin, Ahdar. "Gender in the perspective of the Qur'an." Al-Maiyyah Journal 8 (June 2015): 26. Erviena. "Women's Leadership in the Qur'an: Reinterpretation of M. Quraish Shihab's Thoughts on the Concept of Al-Qawwāmah with the Perspective of Qirā'ah Mubādalah." PTIQ Jakarta Institute E-Thesis, 2021, 199. Fahmi, Izzul. "Locality of the Book of Tafsir al-Ibrīz by KH. Bisri Mustofa." Islamika Inside: Journal of Islam and Humanities 5, no. 1 (June 7, 2019): 96–119. https://doi.org/10.35719/islamikainside.v5i1.36. Faiqoh. "Bisri Mustofa's Interpretation of Verses about Women in the Book of Tafsir al-Ibrīz." Thesis, UIN Sunan Kalijaga Yogyakarta, 2013. https://digilib.uin-suka.ac.id/id/eprint/7662/. Faiqoh, Lili. "Javanese Cultural Interpretation: Study of Interpretation of Luqman's Letter according to KH. Bisri Musthofa." KALAM 10, no. 1 (June 30, 2016): 65–108. https://doi.org/10.24042/klm.v10i1.160. Fauziah, Naili. "Women's Rights in Surah al-Aḥzāb verse 33: A Hermeneutic Approach." El-Tarbawi: Journal of Islamic Education 10 (2017): 21. https://doi.org/10.20885/tarbawi.vol10.iss2.art5. Freyer Stowasser, Barbara. Gender Reinterpretation: Women in the Qur'an, Hadith and Interpretation. 1st ed. Bandung: Hidayah Library, 2001. Gusmian, Islam. Khazanah Tafsir Al-Qur'an Indonesia from Hermeneutics, Discourse to Ideology. Third. Yogyakarta: Salwa Library, 2021. ———. "Interpretation of the Al-Qur'an in Javanese, Strengthening Identity, Ideology, and the Politics of Resistance." Jurnal Suhuf 9 (15 November 2016): 141. https://doi.org/10.22548/shf.v9i1.116. Hidayat, Usman. "The Al-Qur'an Perspective Hijab (Comparative Study of Tafsir fī Ẓilāl al-Qur'ān by Sayyid Quṭb and Tafsir al-Misbah by M. Quraish Shihab)." Repository UIN Banten, tt, 107. Science, Sharifah. "Moral Education Contained in Surah an-Nūr verses 30-31." ETD IAIN Padang Sidimpuan, 2013, 82. Imtyas, Rizkiyatul. "Tafsir al-Ibriz li Ma'rifati Tafsir al-Qur'an by KH Bisri Mustafa." Ushuluna: Ushuluddin Science Journal 1, no. 2 (2015): 64–74. https://doi.org/10.15408/ushuluna.v1i2.15162. Ershad, Al Fikri. "Speciality and Diversity of Languages ​​in Local Interpretation in Indonesia." Journal of Faith and Spirituality 1 (2021): 7. Ismail, Hidayatullah. "Shari'a on Breastfeeding in the Qur'an (Study of Surah al-Baqarah Verse 233)." At-Tibyan Journal: Journal of the Science of the Qur'an and Tafsir 3, no. 1 (9 August 2018): 69. https://doi.org/10.32505/tibyan.v3i1.478. Karvati, Lilis. "Rejecting Gender Subordination based on the Important Role of Women in National Development Ahead of the 2035 Demographic Bonus." PLS Scientific Scholars Journal 5 (December 2020): 9. Maulana. Konco Wingking from Time to Time. Yogyakarta: Diva Press (IKAPI Member), 2021. https://www.researchgate.net/publication/350546570. Mu'awwanah, Nafisatul. "Gender Analysis of Reproductive Verses of Women in the Qur'an." Ijougs: Indonesian Journal of Gender Studies 2 (dd): 17. Mustafa, Bisri. "Tafsir al-Ibrῑz li Ma'rifat Tafsīr al-Qur'ān al-'Azīz bi-Lughah al-Jawiyah." Volume I. Kudus: Menara Kudus, 1960. ———. "Tafsir al-Ibrῑz li Ma'rifat Tafsīr al-Qur'ān al-'Azīz bi-Lughah al-Jawiyah." Volume III. Kudus: Menara Kudus, 1960. ———. "Tafsir al-Ibrῑz li Ma'rifat Tafsīr al-Qur'ān al-'Azīz bi-Lughah al-Jawiyah." Volume II. Kudus: Menara Kudus, 1960. Nuri Azriani, Alfin. "Inter-Relations of the Qur'an and Javanese Culture in Bisri Mustofa's Interpretation of al-Ibrῑz. Digilib UINSA, 2020, 113. Gemsari, Prita. "Communication and Perceptions of Women's Leadership in Javanese Society (The Role of Communication as a Shape for Perceptions of Women's Leadership in Javanese Society)." Kommas Journal, 2016, 20. Rohmad, Abu. "Examine the Characteristics of the Arabic Tafsir-Pegon al-Ibrῑz." Analysis 18 (3 June 2011): 27. https://doi.org/10.18784/analisa.v18i1.122. Rouf, Abdul. "Al-Qur'an in History (Discourse Regarding the History of Al-Qur'an Interpretation)." Al Amin: Journal of Islamic Science and Culture Studies 3 (2020): 17. Sholikhah. "The Fiqh Views of K.H Bisri Mustafa in Tafsir al-Ibrῑz (Study of Verses of Worship)." IAIN Ponorogo E-Thesis, 2017, 129. Suparni, Suparni. "Bisri Mustafa's Interpretation of the Muqatha'ah Letters in Tafsir al-Ibrῑz li Ma'rifat Tafsīr al-Qur'ān al-'Azīz." Repository UIN Jambi, tt, 82. Syamaun, Shukri. "The Concept of Equality in the Discourse of the Qur'an (The Relationship of Men's and Women's Rights and Obligations)." Journal of Al-Bayan: Media Studies and Development of Da'wah Science 22, no. 2 (27 December 2016). https://doi.org/10.22373/albayan.v22i34.882. Shayfi, Sohib, Awra of Menopausal Women (Comparative Study of the Indonesian Ministry of Religion's Translation of the Qur'an and the Translation of Tafsiriyah Muhammad Talib)." PTIQ repository, 2021, 199. Umar, Nasaruddin, Sri Suhandjati Sukri, and Imam Budi Utomo. Understanding of Islam and Challenges to Gender Justice. Cet. 1. Yogyakarta, [Semarang]: Gama Media ; Center for Gender Studies (PSJ) IAIN Walisonggo, 2002. Uyun, Qurotul. "Gender Roles in Javanese Culture." Psychology 13 (tt). https://www.researchgate.net/publication/308705147 Wahyun Muqoyyidin, Andik. "Discourse on Gender Equality: Contemporary Islamic Thoughts on the Islamic Feminism Movement." Al-Ulum Journal (Journal of Islamic Studies) IAIN Gorontalo 13 (2013): 22. Yazdajird Iwanebel, Fejrian. "Mystical Patterns in the Interpretation of KH Bisri Mustafa (Analytical Study of Tafsir al-Ibrῑz)." Rasail Journal 1 (2014): 18. Yuni Mabruri, Audi. "Local Wisdom in the Book of al-Ibriz li Ma'rifah Tafsir Al-Qur'an Al-'Aziz by KH. Bisri Mustofa." Repository UIN Satu, 2018. http://repo.uinsatu.ac.id/11252/. Zamzami. "Women's Testimony in the Qur'an (A Review of the Opinions of Mufassir)." Repository UIN SUSKA, 81. http://repository.uin-suska.ac.id/217/1/2011_201110.pdf. Zubaidi. "Understanding of Misogyny Verses in the Qur'an: (Analysis of Muhammad Mutawalli al-Sya'rawi's Method of Interpretation)." Yudisia: Journal of Legal Thought and Islamic Law 12 (2021): 16.